The Polish Growth Miracle: Outcome of Persistent Reform Efforts - Hartmut Lehmann (Institute for the Study of Labor (IZA), 2012)
Since the beginning of transition in 1990 from a centrally planned to a market oriented economy, the performance of Polands economy has been outstanding if we take GDP growth as our measure. It is not specific reforms that can explain this performance but the radical (big bang) reforms at the beginning of transition in conjunction with persistent efforts during the two decades by all governments to keep on a reform path, no matter what their political orientation. Reforming a centrally planned economy that has very serious macroeconomic disequilibria requires reforms that can be done immediately but also structural or systemic reforms that require years to implement. Both types of reforms will be discussed. In a democratic context reforms can only be undertaken in a sustained way if a majority of voters favours such reform efforts. Even when reform-friendly governments were voted out of office, the new governments in Poland never reversed reforms undertaken by the previous government. This continuous reform stance over two decades is the main cause of the Polish growth miracle. The reasons for the ability of Polish policy makers to pursue economic and administrative reforms in spite of short-run costs to large sections of society will be discussed extensively.
Keywords: D78; J40; P20; P26; 330; policy making; transition economies; political economy of reform; Poland; Systemtransformation; Übergangswirtschaft; Wirtschaftspolitik; Neue politische Ökonomie; Wirtschaftswachstum; Polen